Recipe for success: Creating cornerstone culture for your program - Thorson, M. (Techniques Magazine, 2024)
Many coaches have wondered why some programs have an excellent, thriving culture year after year that everyone wants to be a part of, and why some cultures are much less desirable and often even toxic. What is the secret to developing a great culture? Are there secrets? Is there a model to follow?